Socio-Economic Empowerment of Farmers on Large Scale Plantation: Case Study in Kisaran Subdistrict, North of Sumatra - ., Sismudjito (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTIndonesia has quite enormous potentials in plantation region, one of them is the Province of North Sumatra. The plantations in North Sumatra are distributed in some regions, one of them is Asahan Regency, especially in Kisaran Sub-District. There are two kinds of plantations i.e. the large-scale plantation and the PIR (Estate Smallholders). PIR consists of large scale plantation as nucleus and tradisional smallholders as plasma which allocates their lands manually and is labor intensive. The budidaya of land by traditionally has been inherited from generation to generation so that their farming activities have become routines and has not been able to achieve the maximum production. The efforts to improve the production should be accompanied by a development in human resources by means of empowerment. Supporting factors including providing capital togetherness, Science and Technology, guidance to all citizens as a means to increase production.. Therefore, the development in human resources is meant to improve the plantation production through the society empowerment that goes simultaneously with the improvement in motivation.Keywords: contract-farmaing, smallholder empowermentABSTRAKIndonesia memiliki potensi di bidang perkebunan yang cukup tinggi, salah satunya adalah wilayah Provinsi Sumatera Utara. Perkebunan di wilayah Sumatera Utara tersebar di beberapa daerah,salah satunya adalah daerah Kabupaten Asahan, khususnya di wilayah Kecamatan Kisaran. Ada dua jenis perkebunan yakni perkebunan berskala besar dan Perkebunan Inti Rakyat(PIR). Jenis perkebunan inti rakyat bersifat tradisional dan padat karya. Pembudidayaan lahan secara tradisionalyang diwariskan dari satu generasi ke generasi penerusnya, sehingga aktivitas mereka bertani atau berkebun bersifat rutinitas dan belum dapat mencapai produksi yang maksimal. Dalam upaya meningkatkan produksi harus diiringi dengan peningkatan Sumber Daya Manusia (SDM) melalui pemberdayaan. Faktor-faktor pendukung diantaranya memberikan modal kebersamaan, Ilmu Pengetahuan dan Teknologi (IPTEK), bimbingan kepada para warganya sebagai sarana untuk meningkatkan produksi. Dengan demikian, peningkatan sumber daya manusia ini berfungsi untuk meningkatkan produksi perkebunan melalui pemberdayaan masyarakat yang berjalan seiring dengan meningkatnya motivasi.Kata kunci : pemberdayaan, perkebunan inti rakyat (PIR)